2009
DOI: 10.1007/s00406-009-0869-4
|View full text |Cite
|
Sign up to set email alerts
|

Association study of clock gene (CLOCK) and schizophrenia and mood disorders in the Japanese population

Abstract: Recently the clock genes have been reported to play some roles in neural transmitter systems, including the dopamine system, as well as to regulate circadian rhythms. Abnormalities in both of these mechanisms are thought to be involved in the pathophysiology of major mental illness such as schizophrenia and mood disorders including bipolar disorder (BP) and major depressive disorder (MDD). Recent genetic studies have reported that CLOCK, one of the clock genes, is associated with these psychiatric disorders. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…Far less is known regarding the involvement of circadian genes in the vulnerability to MDD. No evidence of association was found between a CLOCK gene variation in MDD (Bailer et al, 2005;Desan et al, 2000;Kishi et al, 2009a), although a positive association with fluvoxamine response was reported in Japanese MDD patients (Kishi et al, 2009b).…”
Section: Introductionmentioning
confidence: 86%
“…Far less is known regarding the involvement of circadian genes in the vulnerability to MDD. No evidence of association was found between a CLOCK gene variation in MDD (Bailer et al, 2005;Desan et al, 2000;Kishi et al, 2009a), although a positive association with fluvoxamine response was reported in Japanese MDD patients (Kishi et al, 2009b).…”
Section: Introductionmentioning
confidence: 86%
“…Also, our control subjects did not undergo structured interviews. There may also have been a problem of sampling bias with mood disorders; for example, some patients diagnosed with MDD may develop BP in the future [45][46][47] . Second, in this study, we did not apply the 'gene-wide' approach recommended by Ikeda et al [48] to consider population differences.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects in the association analysis were 325 MDD patients (160 males and 165 females; mean age 8 standard deviation 47 were treated with fluvoxamine and diagnosed according to DSM-IV criteria with the consensus of at least two experienced psychiatrists on the basis of a review of medical records and assessments with the Structured Interview Guide for the Hamilton Rating Scale for Depression (SIGH-D). The MDD patients other than these 117 were diagnosed according to DSM-IV criteria with the consensus of at least two experienced psychiatrists on the basis of unstructured interviews and a review of medical records.…”
Section: Subjectsmentioning
confidence: 99%
“…Detailed information on our samples was provided in previous papers. [32][33][34][35] In conclusion, our results suggest that HTR1A may not have a role in the pathophysiology of Japanese MDD patients. On the other hand, according to the meta-analysis, HTR1A was associated with MDD patients, especially in the Asian population.…”
Section: Discussionmentioning
confidence: 58%